KnowledgeBoat Logo

Mathematics

Use the properties of proportionality to solve : 12x+1+2x312x+12x3=32\dfrac{\sqrt{12x + 1} + \sqrt{2x - 3}}{\sqrt{12x + 1} - \sqrt{2x - 3}} = \dfrac{3}{2}.

Ratio Proportion

2 Likes

Answer

Given,

Equation : 12x+1+2x312x+12x3=32\dfrac{\sqrt{12x + 1} + \sqrt{2x - 3}}{\sqrt{12x + 1} - \sqrt{2x - 3}} = \dfrac{3}{2}.

Applying componendo and dividendo we get :

12x+1+2x3+(12x+12x3)12x+1+2x3(12x+12x3)=3+232212x+122x3=512x+12x3=5\Rightarrow \dfrac{\sqrt{12x + 1} + \sqrt{2x - 3} + (\sqrt{12x + 1} - \sqrt{2x - 3})}{\sqrt{12x + 1} + \sqrt{2x - 3} - (\sqrt{12x + 1} - \sqrt{2x - 3})} = \dfrac{3 + 2}{3 - 2} \\[1em] \Rightarrow \dfrac{2\sqrt{12x + 1}}{2\sqrt{2x - 3}} = 5 \\[1em] \Rightarrow \dfrac{\sqrt{12x + 1}}{\sqrt{2x - 3}} = 5

Squaring both sides we get :

(12x+12x3)2=5212x+12x3=2512x+1=25(2x3)12x+1=50x7550x12x=75+138x=76x=7638=2.\Rightarrow \Big(\dfrac{\sqrt{12x + 1}}{\sqrt{2x - 3}}\Big)^2 = 5^2 \\[1em] \Rightarrow \dfrac{12x + 1}{2x - 3} = 25 \\[1em] \Rightarrow 12x + 1 = 25(2x - 3) \\[1em] \Rightarrow 12x + 1 = 50x - 75 \\[1em] \Rightarrow 50x - 12x = 75 + 1 \\[1em] \Rightarrow 38x = 76 \\[1em] \Rightarrow x = \dfrac{76}{38} = 2.

Hence, x = 2.

Answered By

1 Like


Related Questions